Enrollment, Continuity and Factors associated with Health Insurance among Insured and Uninsured People of Pokhara Metropolitan, Kaski - Sharma, Baburam; Bhatta, Bimala (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: To assess SHI and its associated factor among people of Pokhara Metropolitan. Methodology: A comparative study using a cross-sectional design was carried out from June-December, 2018 among 184 insured and Uninsured People of Pokhara Metropolitan, Kaski using multistage sampling technique. Interview method was used using Interview schedule. Data was entered in epidata version 3 and analyzed using SPSS version 20. Result: Educational level (p-value 0.03) was one of the major associated factors to determining enrollment status of SHIP. Similarly home ownership (p-value 0.001) was highly associated factor with insurance status. The association of perceive health status of household with enrollment status (p-value 0.043). Knowledge about SHIP was another major associated factor (p-value 0.02) of enrollment status of SHIP in this study. The study showed that 29% of household have dropout. The major reasons for discontinuity were found as no quality of health care, crowed in service delivery site and long waiting time, inappropriate benefit package, distance to health care facility, did not use service use in last year etc. Conclusion: The major factors such as education, occupation, family income, household ownership, perceive health status and knowledge about social health insurance were found to be associated with enrollment of SHIP